Cytomegalovirus infection is associated with an increase in aortic stiffness in older men which may be mediated in part by CD4 memory T-cells - Kirkham, Frances (2021)
Human Cytomegalovirus (CMV) infection is associated with atherosclerosis, higher cardiovascular disease (CVD) risk, and an increase in memory T-cells (Tmem). T-cells have also been implicated in CVD, independently of CMV infection. To better understand the CMV-associated CVD risk, we examined the association between CMV (IgG) serostatus and central aortic (carotid-to-femoral) pulse wave velocity (cfPWV), an early, independent predictor of CVD. We also investigated if such an association might be reflected by the distribution of Tmem and/or other T-cell subsets. Methods: Healthy older volunteers (60-93 years) underwent routine clinical and laboratory evaluation, including assessment of cfPWV in eligible participants. Flow-cytometry was used to assess proportions of memory T-cells, CD28null T-cells, and CMV-specific T-cells. The following associations were examined; CMV serostatus/cfPWV, CMV serostatus/proportion of Tmem, proportion of Tmem/cfPWV, CD28null T-cells/cfPWV, and CMV-specific T-cells/cfPWV. Linear regression models were used to adjust for age, sex, socioeconomic status, smoking, waist-to-hip ratio, cholesterol, and blood pressure as required. Results: Statistically significant positive associations were found (P-values for the fully adjusted models are given); CMV serostatus/cfPWV in men (P ≤ 0.01) but not in women, CMV serostatus/proportions of CD4 Tmem in men (P ≤ 0.05) but not in women; proportions of CD4 Tmem/cfPWV among CMV seropositive (CMV+) people (P ≤ 0.05) but not CMV seronegative (CMV-) people. Conclusion: CMV infection increases the CVD risk of older men by increasing cfPWV. This may be mediated in part by increased proportions of CD4 Tmem, higher numbers of which are found in CMV+ older people and more so among men than women. Given the high prevalence of CMV worldwide, our findings point to a significant global health issue. Novel strategies to mitigate the increased CVD risk associated with CMV may be required.